Intrafamilial phenotypic variability of the DYT1 dystonia: From asymptomatic TOR1A gene carrier status to dystonic storm - Opal, Puneet; Tintner, Ron; Jankovic, Joseph; Leung, Joanne; Breakefield, Xandra O.; Friedman, Jennifer; Ozelius, Laurie (Movement disorders, 2002)
When primary torsion dystonia is caused by a GAG deletion in the TOR1A gene (DYT1 dystonia), it typically presents with an early‐onset dystonia involving distal limbs, subsequently spreading to a generalized dystonia. We describe a large family with an unusually broad variability in the clinical features of their dystonia both with regard to severity and age of onset. The proband of this family succumbed in his second decade to malignant generalized dystonia, whereas other family members carrying the same mutation are either asymptomatic or display dystonia that may be focal, segmental, multifocal, or generalized in distribution. One family member had onset of her dystonia at age 64 years, probably the oldest reported in genetically confirmed DYT1 dystonia. We conclude that marked phenotypic heterogeneity characterizes some families with DYT1 dystonia, suggesting a role for genetic, environmental, or other modifiers. These findings have implications for genetic testing and counseling. © 2002 Movement Disorder Society.